The Challenge of Public Pension Reform in Advanced and Emerging Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper reviews past trends in public pension spending and provides projections for 27 advanced and 25 emerging economies over 2011-2050. In constructing these projections, the paper incorporates the impact of recent pension reforms and highlights the key assumptions underlying these projections and associated risks. The paper also presents reform options to address future pension spending pressures in the advanced and emerging economies. These reforms-mainly increasing retirement ages, reducing replacement rates, or increasing payroll taxes-are discussed in the context of their role in fiscal consolidation, and their implications for both equity and economic growth. In addition, the paper examines the challenge of emerging economies of expanding coverage in a fiscally sustainable manner.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet